Measuring the Service Quality of Elizabeth Local Brand to Know its Impact on Customer Satisfaction - Karsinah, Karsinah; Mudjiarto, Hari; Taridi, Taridi; Purwandoko, Edi; Meyliana, Henny (LPPM STIAB Jinarakkhita Lampung, 2023)
This study aims to analyze empirical evidence of the effect of service quality on customer satisfaction at the local brand Elizabeth in Bandar Lampung. The problem studied in this study is whether there is a positive relationship between service quality and customer satisfaction at the local brand Elizabeth in Bandar Lampung. The method used in this research is the correlation method. The population in this study were customers of the local Elizabeth brand in Bandar Lampung, where the sample was taken using Proportionate Stratified Random Sampling with a total sample of 122 customers. The instrument reveals the data in a structured scale with five answer choices. The measuring tool to collect data is a questionnaire with 71 item statements. Based on the results of hypothesis testing and simple linear regression, it was obtained that the t value was 38,586 with a significant level of 0.000, while the t table with n = 122 and α = 0.05 received a value of -.678. It can be assumed that t count ≥ t table (38,586 > -.678 or sig < 0.05 (0.000 ≤ 0.05), then Ha is accepted while H 0 is rejected. While the R Square value in this study is 0.925, meaning that service quality is related to customer satisfaction by 93%. Based on the results of the data analysis that has been done, it is concluded that there is a relationship between service quality and customer satisfaction at the local brand Elizabeth in Bandar Lampung. The magnitude of the relationship is 93%, while other factors influence 7%.